Imaging and Discrimination of High-Z Materials with Muon Scattering Tomography - Frazao, Leonor; Maddrell-Mander, S.; Thomay, C.; Velthuis, J.; Steer, C. (Cranfield University, 2017)
Technical paper presented at the 2017 Defence and Security Doctoral Symposium.We have developed methods to define the edges of uranium blocks embedded in concrete, and to discriminate them from different high-Z materials, using muon scattering tomography. There is a need to characterise containers of nuclear waste without having to open them. This is particularly important for legacy waste, which includes large containers with unknown materials. Muon scattering tomography uses as probes the natural occurring cosmic muons, which are highly penetrating particles. Muons undergo multiple Coulomb scattering in matter, and the amount of scattering depends on the atomic number Z of the material, so it is possible to perform imaging of different materials by measuring the incoming and outgoing muon tracks. We carried out simulations in Geant4 of uranium objects of different lengths, enclosed in concrete. These lengths were measured with a new algorithm and compared to the simulated lengths, resulting in a resolution of 0.9 mm, with a 0.2 mm error. The smallest length measured was a uranium sheet with a width of 2 mm. In the material discrimination study, a multivariate analysis was performed with the variables obtained, such as scatter angle distribution, and other correlated variables, in order to distinguish materials from different simulations with the same geometry. Cubic blocks of different sizes and materials were simulated, with sides ranging from 2 cm to 10 cm, with scanning times ranging from a few hours up to 80 hours depending on the sizes of the blocks. From these simulations, we show that it is possible to distinguish uranium blocks from lead, tungsten and plutonium blocks of the same size. The smallest blocks with a good discrimination were cubes with 2 cm side.
Keywords: 'Muon tomography'; 'Nuclear waste'; 'Cosmic rays'; 'DSDS17 technical paper'; 'DSDS17'; 'Nuclear Engineering (incl. Fuel Enrichment and Waste Processing and Storage)'